Academic Communication Research: a Review of Communication Research at the University of Lima (2016-2021) - Chaparro, Hernán (2022)
Little is known about contemporary research on communication in Latin America and, in particular, in Peru. Existing studies show the impact that current research policies have had in academia, the heterogeneity of topics covered, the distance between training and research, the development of research groups, and the type of topics of interest. In order to start an analysis of the scientific production of communication research in Peru, this study offers a descriptive bibliometric approach to the research of students and teachers of the University of Lima’s Faculty of Communication, one of the oldest in the country. The results show the impact of regulatory frameworks on the development of research, the importance of research groups in developing indexed publications and the type of topics that have been addressed.